Pengaruh Iklan, Citra Merek, Kualitas Produk Terhadap Keputusan Pembelian Produk Kecantikan Merek Ms Glow (Studi Pada Mahasiswi Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Rizal Nur Aziz; Agus Widarko; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study uses quantitative research methods, with the aim of knowing the effect of advertising, brand image, product quality on purchasing decisions for MS Glow brand beauty products. Non-probability sampling is the sampling approach, and a purposive sample method based on predetermined criteria is used. Students from FEB UNISMA made up the study's target demographic. 75 respondents made up the study's sample. According to the findings, brand image, advertising, and product quality all have a somewhat favorable and considerable impact on consumers' choice to buy. Additionally, the findings of the simultaneous examination of the independent factors (advertising, brand image, and product quality) have a combined impact on the dependent variable (purchase decision). Keywords: Advertising, Brand Image, Product Quality, and Purchase Decision.